2009
DOI: 10.1093/eurheartj/ehp272
|View full text |Cite
|
Sign up to set email alerts
|

Incremental prognostic value of multi-slice computed tomography coronary angiography over coronary artery calcium scoring in patients with suspected coronary artery disease

Abstract: MSCTA provides additional information to CS regarding stenosis severity and plaque composition. This additional information was shown to translate into incremental prognostic value over CS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
95
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(109 citation statements)
references
References 39 publications
(30 reference statements)
6
95
1
2
Order By: Relevance
“…Similar to other studies published in the literature [6], our results show that the diff erence between culprit lesion's plaque volume in patient with calcium score above 1000 and patients with calcium score below 1000 were statistical signifi cant (p = 0.0002). In case of a cut-off point of calcium score of 600 or even 400, the diff erences between the groups remained statistically signifi cant, even if less expressed.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Similar to other studies published in the literature [6], our results show that the diff erence between culprit lesion's plaque volume in patient with calcium score above 1000 and patients with calcium score below 1000 were statistical signifi cant (p = 0.0002). In case of a cut-off point of calcium score of 600 or even 400, the diff erences between the groups remained statistically signifi cant, even if less expressed.…”
Section: Discussionsupporting
confidence: 90%
“…Th is fi nding helps the clinician in early detection/prevention in asymptomatic patients with low to intermediate risk score (Recommendations for Calcium Scoring Methods Class IIA, IIB: 2010 ACCF/ AHA Guideline for Assessment of Cardiovascular Risk in Asymptomatic Adults: Executive Summary) [7] and in diagnosis of coronary artery disease in symptomatic patients with low and intermediate risk [6,8]. Using this information and assessing our result we had a tendency to manage the intermediate or high risk patients with high calcium score to emergency catheterization laboratory to invasive treatment knowing that this categories of patients is more vulnerable than patients with low calcium score, with less vulnerable lesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, CTCA is more effective at detecting early-stage CAD than functional imaging techniques that assess myocardial perfusion and wall motion 10) . Identifying coronary plaques using CTCA has prognostic value; several studies have demonstrated that the extent of coronary plaques, as determined on CTCA, can predict all-cause mortality and the occurrence of major adverse cardiac events, including cardiac death, myocardial infarction and unstable angina pectoris requiring coronary revascularization [11][12][13][14][15][16] . These findings suggest that conducting risk assessments using CTCA are beneficial for improving the selection of patients who receive aggressive OMT, although it is important to carefully weigh the risk of contrast-induced nephropathy and radiation exposure.…”
Section: Laboratory Measurementsmentioning
confidence: 99%
“…Abbreviations: LDL, low-density lipoprotein; ACE-Is, angiotensinconverting enzyme inhibitors; ARBs, angiotensin Ⅱ receptor blockers; CTCA, computed tomography coronary angiography; CACS, coronary artery calcification score. cardiovascular events [11][12][13][14][15][16] . These studies suggest that with suitable selection of patients, CTCA can be used to identify multiple coronary plaques before the development of fatal CAD, thus enabling the use of aggressive OMT and reducing the incidence of cardiovascular events.…”
Section: Cumulative Effects Of Age Sex a Low Adiponectin Level Dm mentioning
confidence: 99%